Metabolic syndrome and risk of cardiovascular disease in apparently healthy Pakistani adults: a comparative study of different diagnostic criteria - Adil, Syed Omair (2024)
Metabolic syndrome (MetS) is a growing public health concern closely associated with an increased risk of cardiovascular disease (CVD). This study addresses four key objectives: (1) to determine the pooled prevalence of MetS in apparently healthy Pakistani adults through a systematic review and meta-analysis; (2) to assess the prevalence and identify risk factors of undiagnosed MetS among apparently healthy adults living in Karachi, a metropolitan city of Pakistan; (3) to evaluate the role of various anthropometric indices as screening tools for predicting MetS; and (4) to estimate the CVD risk in individuals newly diagnosed with MetS using established risk scores. The meta-analysis included 20 eligible studies, revealing a pooled prevalence of MetS at 28.8% (95% CI: 17.8–39.7). The highest prevalence rates were observed in a sub-urban village of Punjab (68%, 95% CI: 66.6–69.3) and Sindh province (63.7%, 95% CI: 61.1–66.3). Among adults in Karachi, the prevalence of undiagnosed MetS was highest using the modified National Cholesterol Education Program Adul treatment panel III (NCEP-ATP III) criteria (33.9%, 95% CI: 31–36) and lowest with the original NCEP ATP III definition (22.4%, 95% CI: 19–25). Significant risk factors included higher body mass index (BMI), smoking, areca nut use, and low physical activity. In evaluating anthropometric indices, visceral adiposity index (VAI), waist circumference (WC), waist to height ratio (WHtR), and BMI were identified as the most effective associated risk factors of MetS, with area under the curve (AUC) values ranging from 0.641 to 0.820. Finally, CVD risk assessment showed that 59.2% of individuals were classified as low risk by the Framingham Risk Score, while the Globorisk score classified 44.6% as low risk and 21.0% as high risk. A moderate positive correlation (r = 0.651, 95% CI 0.58–0.71) was observed between the two CVD risk scores, with age, gender, and smoking status being significant associated risk factors of 10-year CVD risk. This research highlights the significant burden of MetS and its associated risk factors among the apparently healthy Pakistani population, emphasizing the need for early detection and intervention to prevent future cardiovascular events.